2006
DOI: 10.1111/j.1440-1746.2006.04328.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc L‐carnosine protects against mucosal injury in portal hypertensive gastropathy through induction of heat shock protein 72

Abstract: Zinc derivatives, especially zinc L-carnosine, protected portal hypertensive gastric mucosa with increased hsp72 expression in cirrhotic rats. It is postulated that zinc L-carnosine may be beneficial to the mucosal protection in PHG as a 'chaperone inducer'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…This result may indicate the cytoprotective beneficial impact of these agents against hypoxia induced renal tissue injury. There is an evidence that carnosine and arginine can regulate intracellular HSP-70 expression which is essential for preventing organ dysfunction (Chatterjee et al 2005;Mikami et al 2006;Wu et al 2013) . The current result also revealed that a marked elevation in the serum HIF-1α of hypoxic rats compared with normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…This result may indicate the cytoprotective beneficial impact of these agents against hypoxia induced renal tissue injury. There is an evidence that carnosine and arginine can regulate intracellular HSP-70 expression which is essential for preventing organ dysfunction (Chatterjee et al 2005;Mikami et al 2006;Wu et al 2013) . The current result also revealed that a marked elevation in the serum HIF-1α of hypoxic rats compared with normal animals.…”
Section: Discussionmentioning
confidence: 99%
“…By 8 weeks, a micronodular cirrhosis takes place 31 . It has been used mainly by intraperitoneal injection 12 or oral administration 20 , the dosage 0,2 to 5ml/kg and LC is achieved between 36 hours to 18 weeks 15,20,11,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, they also showed that high and low doses of carnosine affected the catalase or glutathione peroxidase activities at the same rate. Generally, the cumulative dose of carnosine administered is approximately 250-300 mg/ kg [19][20][21]. All efforts were made to minimize animal suffering and to reduce the number of animals used in this experiment.…”
mentioning
confidence: 99%